Fabrication of a working fluid filler for cooling photovoltaic module - Supriyono, Toto; Omar, Ghazali; Tamaldin, Noreffendy; Sonawan, Hery; Novahardi, Mi’raj; Sidik, Fachrul; Sumartono, M. R.; Kasim, M. S. (BKS-TM Indonesia, 2023)
This paper discusses manufacturing a special tool (Filler) to fill the working fluid of a photovoltaic module (PVM) cooler. PVM needs to be cooled because its performance is susceptible to temperature changes. An increase in PVM temperature can reduce its performance. Due to their low thermal resistance, heat pipes can be used as PVM coolers. The greatest heat release occurs through the evaporation process of the working fluid within the heat pipe. The filling of the working fluid into the heat pipe is carried out under vacuum pressure, so a special tool or a special filler is required so that the filling of the working fluid corresponds to the specified amount. The filler consists of a liquid reservoir (water tank and support), an isolation valve, a check valve, and a liquid transfer pipe. The manufacture of the filler has been performed in several stages, from material selection to fabrication and assembly of parts. The assembly of the parts of the copper material was performed using the brazing joint method, while for the thread parts, a seal tape was added, combining the top and bottom of the tank using epoxy glue. The water tank support and tables were fabricated using 3D printing. Copper pipes 12.7 mm (1/2 inch) were cut to obtain a length of 50 mm, as many as six pieces, for the acrylic pipe cut along 48 mm. The acrylic sheets were cut in a circle with a diameter of 60 mm, as many as two pieces, and holes and grooves in the middle, in sizes M6 and M16. After the cutting process is complete, assemble the filler parts by connecting the brazing, threading, and gluing processes. The support table has dimensions of 150 mm x 150 mm and a height of 125 mm made using a 3D printing process. The results of the filler function test show that the filler that has been made can be used to vacuum the heat pipe or PVM coolant and fill the working fluid according to the specified amount.